PEMODELAN DETEKSI PENYAKIT SIROSIS HATI DENGAN MENGGUNAKAN JARINGAN SYARAF TIRUAN - Fajar Y Zebua; Sri Hasta Mulyani; Marselina Endah H. (SISFOTENIKA, 2012)
Abstract : Liver (liver) is the largest organ in the human body. In the hearts of many important processes occur in human life. Unfortunately, although the liver is essential for life, the liver is also susceptible to disease. Cirrhosis of the liver is one type of heart disease. Cirrhosis of the liver is a common chronic liver disease, caused by damage to the liver. Our research was made of a disease modeling to simulate using neural networks with backpropagation method to determine the causes and symptoms of liver cirrhosis. Modeling is expected to detect the disease early cirrhosis of the liver so it can be preventative or further action. Keywords: liver, cirrhosis of the liver, neural networks, backpropagation.